Fixed Point Theorems for Manageable Contractions with Application to Integral Equations - N. Hussain; I. Iqbal; Badriah A. S. Alamri; M. A. Kutbi (Journal of Function Spaces, 2017)
In this paper we utilize the concept of manageable functions to define multivalued α⁎-η⁎ manageable contractions and prove fixed point theorems for such contractions. As applications we deduce certain fixed point theorems which generalize and improve Nadler’s fixed point theorem, Mizoguchi-Takahashi’s fixed point theorem, and some other well-known results in the literature. Also, we give an illustrating example showing that our results are a proper generalization of Nadler’s theorem and provide an application to integral equations.